Strain Accumulation and Microstructural Evolution During Friction Stir Welding of Pure Magnesium - Li, Zhuoliang; Ding, Hua; Chen, Yu; Li, Jizhong; Liu, Lizhong (Frontiers in Materials, 2020)
In this study, the stain accumulation processes of pure Mg material during FSW processes with different rotation speeds are measured and calculated and the microstructure is characterized. Copper foil is inserted as a marker to reveal the flow of pure Mg. The results indicate that the strain accumulation process can be divided into three stages, acceleration stage, high velocity flow stage and decelerate & constant velocity flow stage, respectively. The speed of strain accumulation is relatively low in acceleration stage and high velocity flow stage, while it becomes really high in decelerate & constant velocity flow stage. The higher the speed of rotation, the more severe plastic deformation occurs within the material. The accumulated strain of pure Mg are 12.8 and 14.5 at the rotation speed of 1000rpm and 1500rpm, respectively. Relatively believable equations are established by calculation and derivation. It can be seen from the microstructure that pure Mg material has experienced an obviously grain growth process follows by significantly refinement during the FSW deformation. High temperature field caused by friction is the main reason which leads to the grain growth.